Mural Batik Nusantara Sebagai Eksposure Apresiasi Visual Batik di Dinding Dinsos Jabar - Suprayogi, Bambang Meiga; Iskandar, Muhamad (ATRAT: Jurnal Seni Rupa, 2025)
Batik motifs in the heritage of cultural arts are cultural assets that become characteristics, strong characters that are identical, of a region. Batik motifs that appear with various symbols of local wisdom of a particular region, show configurations that create a depth of meaning, ultimately providing cultural norms and values that are full of meaning. Along with the phenomenon of diversity, cultural assets of a region become a shared pride of the nation, so that territorial boundaries are no longer an obstacle when batik motifs have a cultural impact for a wider scope, when other regions, or government institutions want to attach this aspect of causality, so that it has a greater impact on uniting brotherhood, the power of nationalism, patriotism, which can be put forward, as an adage of diversity requirements, a representative manifestation in popular mural culture that is applied to the West Java Social Service institution, as part of the exposure of batik motifs as a treasure of civilization and national culture that is to be highlighted there, through the application of mural images of Indonesian batik motifs on the walls of the West Java Social Service.